(untitled) (Revista Española de Estudios Agrosociales y Pesqueros, 2023)
Considering the advance of a global food system toward industrialized agricultural production, large-scale monocultures, dependence on fossil fuels, long chains of distribution and sales increasingly monopolized, local projects and strategies are driven by different social actors who promote the production, distribution, transformation, commercialization / exchange and consumption of food, including ecological, proximity and democratic practices as well as elements of the Social and Solidarity Economy (ESS). This document aims to analyze the potential environmental, economic, social, cultural and political impacts of agroecological markets, taking through the experience, trajectory and learning of the so-called Tianguis Alternativo de Puebla, located in Mexico, considering its path of 15 years of existence. Through qualitative and quantitative methodologies, the incidence of this market in the territory is shown. The results of this investigations show the territorial impacts in the productive, organizational, sociocultural, commercial and exchange processes, as well as consumption; promoting the quality and quantity of available local agroecological foods, politicizing exchange relationships, and building network and links between the different social actors involved in the market.